CONSTRUCTING ISLAMIC IDENTITY AMONG UINSA STUDENTS THROUGH ENGAGEMENT WITH INSTAGRAM REELS - Fadya Majida Az-Zahra; Fikry Zahria Emeraldien (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2025)
This study looks to understand the meaning making process and identity formation among UINSA (Sunan Ampel Islamic State University) students surrounding the phenomenon of reels on Instagram along the visual consumerism continuum. The work focuses on the phenomenological qualitative method used in the interviews and stimulated recall. The results reveal the following. For the most part, short Islamic videos and the viewers’ emotional and cognitive shifts suggest varying degrees of motivational and spiritual awareness and reflection. Secondly, the platform has become an identity construction site where students have become netizens, and, in Islamic education, they intermingle education, personality, and algorithms into varying, at times, unique frameworks. Third, the platform influences behavioral tendencies, from subtle shifts in daily religious habits to increased trust in digital preachers, while also reinforcing the need for critical filtering to avoid superficiality and misinformation. The study concludes that Instagram reels are beyond serving as entertainment oriented content, playing a significant role in shaping emotional engagement, spiritual resonance, and being the dynamic formation of contemporary muslim youth identity.